The role of the Manpower and Transmigration Office in supervising Manpower Service Companies (PJTKI) in sending Indonesian Migrant Workers (TKI) abroad - Ketut Meta (University of Merdeka Malang, 2005)
This research was conducted at PT. Ficotama Bina Trampil Malang handles the sending of TKI abroad to Hong Kong. The TKI who was dispatched to Hong Kong worked as a housemaid (housekeeper). Apart from PT. Ficotama Bina Trampil Malang was also carried out at the Malang Manpower and Transmigration Office. The results of the study show that TKI and PJTKI often commit violations in the work agreement, do not meet the health, age, or skills requirements of the prospective TKI, TKI who change employers without reporting to the PJTKI, do not report contract extensions, run away from employers and so on. Meanwhile, the Manpower and Transmigration Office in supervising PJTKIs still has violations, especially in implementing regulations regarding the placement of Indonesian Migrant Workers abroad, for example, incomplete documents for the departure of prospective TKI abroad such as work visas or work agreements.